2007
DOI: 10.1111/j.1095-8649.2007.01337.x
|View full text |Cite
|
Sign up to set email alerts
|

Swimming alters responses to hypoxia in the Adriatic sturgeon Acipenser naccarii

Abstract: When the Adriatic sturgeon Acipenser naccarii was exposed to progressive hypoxia under static conditions, it exhibited a linear decline in O 2 uptake, behaving as an 'oxyconformer'. When, however, it was allowed to swim at a low sustained speed, it could regulate O 2 uptake down to a mean AE S.E. critical P O2 (P crit ) of 4Á9 AE 0Á5 kPa (n ¼ 6). At moderate levels of hypoxia, static fish exhibited significant reductions in arterial blood O 2 content, and increases in plasma lactate, which were not observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…4). This observation would support the findings of Crocker and Cech (1997), who concluded that white sturgeon exposed to even moderate hypoxia became hypometabolic (i.e., reduce their metabolic rate), a hypothesis supported by other studies (Burggren and Randall 1978;McKenzie et al 2007). Thus, an increased OBF may provide a mechanism to increase oxygen uptake and maintain tissue oxygen perfusion under moderate hypoxia, but cannot support aerobic metabolism when oxygen content in the water and diffusion gradients driving O 2 movement are very low (i.e., in this case, when water PO 2 is B10 mm Hg).…”
Section: Strategies Of Hypoxia Tolerance In Sturgeonsupporting
confidence: 86%
See 2 more Smart Citations
“…4). This observation would support the findings of Crocker and Cech (1997), who concluded that white sturgeon exposed to even moderate hypoxia became hypometabolic (i.e., reduce their metabolic rate), a hypothesis supported by other studies (Burggren and Randall 1978;McKenzie et al 2007). Thus, an increased OBF may provide a mechanism to increase oxygen uptake and maintain tissue oxygen perfusion under moderate hypoxia, but cannot support aerobic metabolism when oxygen content in the water and diffusion gradients driving O 2 movement are very low (i.e., in this case, when water PO 2 is B10 mm Hg).…”
Section: Strategies Of Hypoxia Tolerance In Sturgeonsupporting
confidence: 86%
“…This lack of clear patterns in the response to hypoxia in sturgeon may also reflect a lack of a consistent methodology to produce hypoxia (e.g., rapid versus graded hypoxia, water temperature, fish size or level of hypoxia; see Table 2 and Perry et al 2009). Complicating things further is the recent discovery that swimming (McKenzie et al 2007) and diet (McKenzie et al 1997) can alter the hypoxia response in sturgeon.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…If aquatic P O2 drops toward P crit , the resulting hypoxia-induced drop in AS may cause important eco-physiological functions such as growth, activity and reproduction to be compromised (Chabot and Claireaux, 2008a). Major life-threatening processes are challenged at P O2 <P crit as the fish is forced into an oxygen-conforming state (McKenzie et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Under sustained decreases of DO concentration, fish try to main-tain their standard metabolic rate until they reach the P crit (McKenzie et al 2007). Below the P crit , fish survival is usually limited to a few minutes or hours (Barrionuevo et al 2010).…”
Section: Resultsmentioning
confidence: 99%